The Role of Islamic Banking in Promoting Financial Inclusion - Ranisya Cika Alfiani; Siti Lestari; Sumarta Sumarta; Hudallah Hudallah (Penerbit Hellow Pustaka, 2026)
This study aims to analyze the role of Islamic banking in encouraging financial inclusion in Indonesia. Financial inclusion is the main focus of economic development programs, with the aim of providing broader and more equitable financial access for all levels of society. This study is motivated by the still limited level of financial inclusion in Indonesia, especially for people who have not been served by formal financial institutions. The purpose of this study is to identify the contribution of Islamic banks in expanding financial access and to understand the obstacles and opportunities faced. This study uses a qualitative approach with secondary data analysis, including Islamic bank financial reports, data from the Financial Services Authority (OJK), and related literature reviews. This study also uses a qualitative approach to gather in depth insights on this topic. Qualitative data were analyzed using Strauss and Corbin’s grounded theory, which involved three main steps: open coding, axial coding, and selective coding. The main findings indicate that Islamic banks have a strategic role in increasing financial inclusion through inclusive Sharia-based products, such as microfinance, interest-free savings, and technology-based digital services. The implication is that improving Islamic financial education and developing digital technology are needed to expand the reach of services. In conclusion, Islamic banks play an important role in supporting financial inclusion by providing financial access to underserved communities. Better collaboration, regulatory support, and development of Sharia-compliant financial products can expand financial inclusion.